Resin Film
Patent Information
- Application Number
- JP2024516126
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-18
- Filing Date
- 2023-03-08
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2043-03-08
Smart Images

Figure 0007635883000015 
Figure 0007635883000016 
Figure 0007635883000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a resin film. [Background technology]
[0002] In recent years, high-end information and communication devices capable of information communication using high frequency bands utilizing 5G have been commercialized. Multilayer boards mounted on such information and communication devices are manufactured from, for example, copper clad laminates (CCLs). CCLs include resin films. The resin composition constituting the resin film preferably has a low dielectric constant and a low thermal expansion coefficient to reduce warping of the CCL. In addition, in order to achieve Beyond 5G and 6G, which will enable even higher speed and larger capacity communication, resin compositions with even lower dielectric constants are required from the viewpoint of improving high frequency characteristics.
[0003] Conventional resin compositions are disclosed in Japanese Patent No. 5199569 (Patent Document 1), Japanese Patent Publication No. 2020-147677 (Patent Document 2), Japanese Patent No. 4967116 (Patent Document 3), and Japanese Patent Publication No. 2007-231144 (Patent Document 4).
[0004] Patent Document 1 discloses a low dielectric resin composition containing hollow particles consisting of a shell and a hollow portion and a thermosetting resin, in which 98% by mass or more of the entire shell of the hollow particles is formed of silica. Patent Document 2 discloses a resin molded product containing an insulating resin and hollow particles having a shell layer containing silsesquioxane. Patent Document 3 discloses a multilayer circuit board having an insulating layer composed of a porous insulating layer formed by dispersing a particulate material in a synthetic resin and a non-porous insulating layer. An example of the particulate material is aerogel. Patent Document 4 discloses a resin composition constituting a resin layer of a wiring board, the resin composition containing a low dielectric constant resin and a zeolite.
[0005] In addition, conventional resin compositions are disclosed in JP 2019-183005 A (Patent Document 5), WO 2008 / 081885 A (Patent Document 6), JP 2007-154169 A (Patent Document 7), JP 2021-046538 A (Patent Document 8), JP 2003-147166 A (Patent Document 9), JP-B-7-099646 A (Patent Document 10), JP 2008-075079 A (Patent Document 11), and Japanese Patent No. 6865687 Specification (Patent Document 12). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5199569 specification [Patent Document 2] JP 2020-147677 A [Patent Document 3] Patent No. 4967116 specification [Patent Document 4] JP 2007-231144 A [Patent Document 5] JP 2019-183005 A [Patent Document 6] International Publication No. 2008 / 081885 [Patent Document 7] JP 2007-154169 A [Patent Document 8] Patent Publication No. 2021-046538 [Patent Document 9] JP 2003-147166 A [Patent Document 10] Special Publication No. 7-099646 [Patent Document 11] JP 2008-075079 A [Patent Document 12] Patent No. 6865687 specification Summary of the Invention [Problem to be solved by the invention]
[0007] In this way, in the resin composition constituting the resin film to be used in the multilayer board, the addition of various types of fillers to the resin component has been proposed from the viewpoint of improving various physical properties. However, there is still room for improvement in the resin composition constituting the resin film suitable for use in the multilayer board from the viewpoint of reducing the relative dielectric constant and the thermal expansion coefficient.
[0008] The present disclosure has been made in consideration of the above problems, and has an object to provide a resin film that can be suitably used in multilayer boards. [Means for solving the problem]
[0009] The resin film based on the present disclosure is made of a resin composition including a resin component and a covalent organic framework in which a plurality of linker moieties and a plurality of multidentate core moieties are linked by covalent bonds.
[0010] According to the present disclosure, since the covalent organic framework has a mesh-like molecular skeleton containing air with a low relative dielectric constant, when the resin component has a relatively high relative dielectric constant, the relative dielectric constant of the resin composition can be made lower than that of the resin component. Furthermore, since the mesh-like molecular skeleton of the covalent organic framework has covalent bonds and is rigid, when the resin component has a relatively high linear expansion coefficient, the linear expansion coefficient of the resin composition can be made lower than that of the resin component. Effect of the Invention
[0011] The resin film according to the present disclosure can be suitably used for multilayer substrates. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a perspective view showing a resin film according to an embodiment of the present disclosure. [Diagram 2] FIG. 1 is a perspective view showing a schematic structure of a two-dimensional COF of a covalent organic framework according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present disclosure will be described. In the drawings, the same or corresponding parts are denoted by the same reference characters, and the description thereof will not be repeated.
[0014] [Resin film] 1 is a perspective view showing a resin film according to an embodiment of the present disclosure. The resin film 1 according to an embodiment of the present disclosure is made of a resin composition containing a resin component and a covalent organic framework, and can be suitably used as a low dielectric layer included in a multilayer resin substrate such as a flexible substrate or a rigid substrate (particularly, a circuit substrate for high frequency). The thickness of the resin film 1 is, for example, 10 μm or more and 250 μm or less.
[0015] <Resin composition> The resin composition according to the present embodiment preferably has a water absorption rate of 0.1% by mass or less when immersed in water at room temperature for 24 hours. Water has a relatively high dielectric constant. Therefore, if the water absorption rate is 0.1% by mass or less, the resin film made of the resin composition is prevented from varying in dielectric constant due to water absorption, and can be more suitably used as a circuit board member for high frequency applications.
[0016] The melting point (Tm) of the resin composition according to the present embodiment is preferably above 300°C. If the melting point (Tm) of the resin composition is above 300°C, the resin film made of the resin composition has good heat resistance, and therefore can be suitably used for high-voltage circuit boards. The melting point (Tm) of the resin composition is measured based on the measurement of the storage modulus (E') using a dynamic viscoelasticity measuring device. Specifically, the melting point (Tm) of the resin composition is the temperature of the inflection point on the high-temperature region side of the storage modulus (E').
[0017] The resin composition according to the present embodiment preferably has a relative dielectric constant of less than 3.0, more preferably less than 2.8, and even more preferably less than 2.6, when measured by applying a high-frequency signal of 30 GHz at an ambient temperature of 25° C. using a cavity resonator method in accordance with JIS R 1641. If the relative dielectric constant of the resin composition is less than 3.0, when the resin film is used in a high-frequency circuit board, the transmission loss in the board can be more effectively suppressed.
[0018] The resin composition according to the present embodiment preferably has a dielectric loss tangent of less than 0.002, more preferably less than 0.001, when measured by applying a high-frequency signal of 30 GHz at an ambient temperature of 25° C. using a cavity resonator method in accordance with JIS R 1641. If the dielectric loss tangent of the resin composition is less than 0.002, when the resin film is used in a high-frequency circuit board, the transmission loss in the board can be more effectively suppressed.
[0019] The resin composition according to the present embodiment, when formed into a film, preferably has a linear expansion coefficient in an in-plane direction of less than 59 ppm / ° C., more preferably 40 ppm / ° C. or less, and even more preferably 20 ppm / ° C. or less. If the linear expansion coefficient is less than 59 ppm / ° C., warping of a circuit board can be effectively suppressed when the circuit board is manufactured using a resin film made of the resin composition.
[0020] (Resin component) Next, the resin component contained in the resin composition will be described. The resin component according to this embodiment is a thermoplastic resin or a thermosetting resin. When the resin component is a thermoplastic resin, the resin film can be suitably used for a flexible substrate. In addition, the resin component is appropriately selected from the viewpoint of electrical properties such as low relative dielectric constant or dielectric tangent, low water absorption, or heat resistance. For this reason, examples of the thermoplastic resin include cyclic olefin resins, chain olefin resins, fluorine resins, styrene resins, and liquid crystal polymers. In addition, when the resin component is a thermosetting resin, the resin film can be suitably used for a rigid substrate. Examples of the thermosetting resin include polyimide.
[0021] Examples of the cyclic olefin polymer include addition polymers of cyclic olefin monomers and ring-opening polymers of cyclic olefin monomers.
[0022] Examples of the addition polymer of a cyclic olefin monomer include an addition (co)polymer of a norbornene type monomer obtained by polymerizing a norbornene type monomer, and an addition (co)polymer of a norbornene type monomer and ethylene, an α-olefin or a non-olefin. together and addition copolymers with other monomers such as cyclic dienes. The addition polymers of these cyclic olefin monomers can be obtained by known polymerization methods. Commercially available addition polymers of cyclic olefin resins include "TOPAS (registered trademark)" (manufactured by Ticona) and "Apel (registered trademark)" (manufactured by Mitsui Chemicals), which are addition copolymers of norbornene and ethylene.
[0023] The addition polymer of a cyclic olefin monomer is preferably an addition polymer of a norbornene type monomer obtained by addition polymerization of a norbornene type monomer (hereinafter, sometimes simply referred to as "polynorbornene"). Polynorbornene has relatively low water absorption, high heat resistance, and a low dielectric constant. For this reason, by using polynorbornene as a resin component, a resin film having low water absorption, high heat resistance, and a low dielectric constant can be obtained.
[0024] Examples of the addition polymer of norbornene type monomers include those containing a repeating unit represented by the following general formula (1). [ka] [X in formula (1) represents -CH2-, -CH2CH2-, or -O-; R 1 , R 2 , R 3 , R 4 each independently represents a hydrogen atom, a hydrocarbon group, a polar group having 1 to 12 carbon atoms, or an organic group containing the polar group. n represents an integer of 0 to 2, and the number of repetitions may vary.]
[0025] R 1 , R 2 , R 3 , R 4 At least one of the groups is preferably a cyclic ether group having 1 to 12 carbon atoms, an organic group having a reactive double bond, or a group containing an alkoxysilyl group.
[0026] Examples of the polar group having 1 to 12 carbon atoms include a hydroxyl group, a carboxyl group, an ester group, an acryloyl group, a methacryloyl group, a silyl group, an epoxy group, a ketone group, an ether group, etc. Specific examples of the silyl group include alkoxysilyl groups such as a trimethoxysilyl group and a triethoxysilyl group.
[0027] Examples of the organic group containing a polar group having 1 to 12 carbon atoms include those in which the polar group is bonded to a norbornene skeleton via a linear or branched alkyl group, an alkenyl group, an alkynyl group, an aralkyl group, a cyclic aliphatic group, an aryl group, an ether group, or a ketone group. Specific examples of alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl groups; specific examples of alkenyl groups include vinyl, allyl, butynyl, and cyclohexenyl groups; specific examples of alkynyl groups include ethynyl, 1-propynyl, 2-propynyl, 1-butynyl, and 2-butynyl groups; specific examples of aralkyl groups include benzyl and phenethyl groups; specific examples of cyclic aliphatic groups include cyclopentyl, cyclohexyl, and cyclooctyl groups; and specific examples of aryl groups include phenyl, naphthyl, and anthracenyl groups.
[0028] Specific examples of the organic group containing a polar group having 1 to 12 carbon atoms include an organic group containing a silyl group and an organic group containing an epoxy group. A specific example of the organic group containing a silyl group is a diphenylmethylsilyl group. 、 Specific examples of organic groups containing an epoxy group, such as a triethoxysilylethyl group, a trimethoxysilylpropyl group, and a trimethylsilylmethyl ether group, include an allylglycidyl ether group, an allylglycidyl ether group, etc. However, the polynorbornene in the present disclosure is not limited to these.
[0029] As the norbornene type monomer used for producing an addition polymer (polynorbornene) of a norbornene type monomer, a norbornene type monomer containing 2-norbornene and represented by the following general formula (2) is preferable. [ka] [X in formula (2) represents -CH2-, -CH2CH2-, or -O-; R 1 , R 2 , R 3 , R4 each independently represents a hydrogen atom, a hydrocarbon group, a polar group having 1 to 12 carbon atoms, or an organic group containing the polar group. n represents an integer of 0 to 2, and the number of repetitions may be different.]
[0030] Examples of norbornene-type monomers having an alkyl group include 5-methyl-2-norbornene, 5-ethyl-2-norbornene, 5-propyl-2-norbornene, 5-butyl-2-norbornene, 5-pentyl-2-norbornene, 5-hexyl-2-norbornene, 5-heptyl-2-norbornene, 5-octyl-2-norbornene, 5-nonyl-2-norbornene, and 5-decyl-2-norbornene.
[0031] Examples of norbornene-type monomers having an alkenyl group include 5-allyl-2-norbornene, 5-methylidene-2-norbornene, 5-ethylidene-2-norbornene, 5-isopropylidene-2-norbornene, 5-(2-propenyl)-2-norbornene, 5-(3-butenyl)-2-norbornene, 5-(1-methyl-2-propenyl)-2-norbornene, 5-(4-pentenyl)-2-norbornene, 5-(1-methyl-3-butenyl)-2-norbornene, 5-(5-hexenyl)-2-norbornene, 5-(1-methyl-4- pentenyl)-2-norbornene, 5-(2,3-dimethyl-3-butenyl)-2-norbornene, 5-(2-ethyl-3-butenyl)-2-norbornene, 5-(3,4-dimethyl-4-pentenyl)-2-norbornene, 5-(7-octenyl)-2-norbornene, 5-(2-methyl-6-heptenyl)-2-norbornene, 5-(1,2-dimethyl-5-hexenyl)-2-norbornene, 5-(5-ethyl-5-hexenyl)-2-norbornene, 5-(1,2,3-trimethyl-4-pentenyl)-2-norbornene, and the like.
[0032] An example of a norbornene type monomer having an alkynyl group is 5-ethynyl-2-norbornene.
[0033] An example of a norbornene type monomer having a silyl group is 1,1,3,3,5,5-hexamethyl-1,5-dimethylbis((2-(5-norbornen-2-yl)ethyl)trisiloxane.
[0034] As a norbornene type monomer having an alkoxysilyl group, dimethylbis((5-norbornen-2-yl)methoxy) ) Silane, 5-trimethoxysilyl-2-norbornene, 5-triethoxysilyl-2-norbornene, 5-(2-trimethoxysilylethyl)-2-norbornene, 5-(2-triethoxysilylethyl)-2-norbornene, 5-(3-trimethoxypropyl)-2-norbornene, 5-(4-trimethoxybutyl)-2-norbornene, 5-trimethylsilyl methyl ether-2-norbornene, and the like.
[0035] Examples of norbornene-type monomers having an aryl group include 5-phenyl-2-norbornene, 5-naphthyl-2-norbornene, and 5-pentafluorophenyl-2-norbornene, and examples of norbornene-type monomers having an aralkyl group include 5-benzyl-2-norbornene, 5-phenethyl-2-norbornene, 5-pentafluorophenylmethane-2-norbornene, 5-(2-pentafluorophenylethyl)-2-norbornene, and 5-(3-pentafluorophenylpropyl)-2-norbornene.
[0036] Examples of norbornene-type monomers having a hydroxyl group, an ether group, a carboxyl group, an ester group, an acryloyl group, or a methacryloyl group include 5-norbornene-2-methanol and its alkyl ethers, 5-norbornene-2-methyl ester of acetate, 5-norbornene-2-methyl ester of propionate, 5-norbornene-2-methyl ester of butyrate, 5-norbornene-2-methyl ester of valerate, 5-norbornene-2-methyl ester of caproate, 5-norbornene-2-methyl ester of caprylate, 5-norbornene-2-methyl ester of caprate ... and 5-norbornene-2-methyl ester of caprate. norbornene-2-methyl ester, lauric acid 5-norbornene-2-methyl ester, stearic acid 5-norbornene-2-methyl ester, oleic acid 5-norbornene-2-methyl ester, linolenic acid 5-norbornene-2-methyl ester, 5-norbornene-2-carboxylic acid, 5-norbornene-2-carboxylic acid methyl ester, 5-norbornene-2-carboxylic acid ethyl ester, 5-norbornene-2-carboxylic acid t-butyl ester, 5-norbornene-2-carboxylic acid i-butyl ester, 5-norbornene-2-capric acid carboxylic acid trimethylsilyl ester, 5-norbornene-2-carboxylic acid triethylsilyl ester, 5-norbornene-2-carboxylic acid isobornyl ester, 5-norbornene-2-carboxylic acid 2-hydroxyethyl ester, 5-norbornene-2-methyl-2-carboxylic acid methyl ester, cinnamic acid 5-norbornene-2-methyl ester, 5-norbornene-2-methylethyl carbonate, 5-norbornene-2-methyl n-butyl carbonate, 5-norbornene-2-methyl t-butyl carbonate, 5-methoxy-2- Norbornene, (meth)acrylic acid 5-norbornene-2-methyl ester, (meth)acrylic acid 5-norbornene-2-ethyl ester, (meth)acrylic acid 5-norbornene-2-n-butyl ester, (meth)acrylic acid 5-norbornene-2-n-propyl ester, (meth)acrylic acid 5-norbornene-2-i-butyl ester, (meth)acrylic acid 5-norbornene-2-i-propyl ester, (meth)acrylic acid 5-norbornene-2-hexyl ester, (meth)acrylic acid 5-norbornene-2-octyl ester,(Meth)acrylic acid 5-norbornene-2-decyl ester, etc.
[0037] An example of a norbornene type monomer having an epoxy group is 5-[(2,3-epoxypropoxy)methyl]-2-norbornene.
[0038] Norbornene-type monomers consisting of a tetracyclo ring include 8-methoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-ethoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-n-propylcarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-i-propylcarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-n-butoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-(2-methylpropoxy)carbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-(1-methylpropoxy)carbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-t-butoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-cyclohexyloxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-(4'-t-butylcyclohexyloxy)carbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-phenoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-tetrahydrofuranyloxycarbonyltetracyclo[4.4.0.1 2,5.1 7,10 ]-3-dodecene, 8-tetrahydropyranyloxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-methoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-ethoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-n-propoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-i-propoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-n-butoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-(2-methyl P 4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-(1-methyl P 4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-t-butoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-cyclohexyloxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-(4'-t-butylcyclohexyloxy)carbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-phenoxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyl-8-tetrahydrofuranyloxycarbonyltetracyclo[4.4.0.1 2,5 .17,10 ]dodec-3-ene, 8-methyl-8-tetrahydropyranyloxycarbonyltetracyclo[4.4.0.1 2,5 .1 7,10 ]-3-dodecene, 8-methyl-8-acetoxytetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8,9-di(methoxycarbonyl R Bonyl)tetracyclo[4.4.0.1 2,5 .1 7,10 ]Dodec-3-ene, 8,9-di(ethoxyca R Bonyl)tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8,9-di(n-propoxyca R Bonyl)tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8,9-di(i-propoxyca R Bonyl)tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8,9-di(n-butoxyca R Bonyl)tetracyclo[4.4.0.1 2,5 .1 7,10 ]Dodec-3-ene, 8,9-di(t-butoxyca R Bonyl)tetracyclo[4.4.0.1 2,5 .1 7,10 ]Dodec-3-ene, 8,9-di(cyclohexyloxycarbonyl) R Bonyl)tetracyclo[4.4.0.1 2,5 .1 7,10 ]Dodec-3-ene, 8,9-di(phenoxyloxyca R Bonyl)tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8,9-di(tetrahydrofuranyloxycarbonyl)tetracyclo[4.4.0.1 2,5 .1 7,10 ]-3-dodecene, 8,9-di(tetrahydropyranyloxycarbonyl)tetracyclo[4.4.0.1 2,5 .1 7,10 ]-3-dodecene, 8,9-tetracyclo[4.4.0.12,5 .1 7,10 ]dodec-3-ene, tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene-8-carboxylic acid, 8-methyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene-8-carboxylic acid, 8-methyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-ethyltetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, 8-methyltetracyclo[4.4.0.1 2,5 .0 1,6 ]dodec-3-ene, 8-ethylidenetetracyclo[4.4.0.1 2,5 .1 7,12 ]dodec-3-ene, 8-ethylidenetetracyclo[4.4.0.1 2,5 .1 7,10 0 1,6 ]Dodec-3-ene, etc.
[0039] Examples of ring-opening polymers of cyclic olefin resins include ring-opening (co)polymers of norbornene type monomers, hydrogenated ring-opening (co)polymers of norbornene type monomers, and norbornene type monomers and ethylene, α-olefins or non-olefins. together Examples of the ring-opening copolymer include a ring-opening copolymer with other monomers such as a diolefin, and a hydrogenated ring-opening copolymer of a norbornene type monomer and ethylene, α-olefins, or a norbornene type monomer. As the ring-opening polymer of a cyclic olefin resin, a hydrogenated ring-opening copolymer of a norbornene type monomer is preferable. A hydrogenated ring-opening copolymer of a norbornene type monomer has a relatively low water absorption and a low dielectric constant. For this reason, by using a hydrogenated ring-opening copolymer of a norbornene type monomer as a resin component, a resin film with low water absorption and a low dielectric constant can be obtained. In addition, examples of commercially available ring-opening polymers of a cyclic olefin resin include "ZEONOR (registered trademark)", "ZEONEX (registered trademark)" (manufactured by Nippon Zeon Co., Ltd.), and "ARTON (registered trademark)" (manufactured by JSR Corporation).
[0040] The chain olefin resin is an olefin resin that does not have a cyclic structure. Examples of the chain olefin resin include chain polyolefin resins such as polyethylene resins, polypropylene resins, and polymethylpentene resins. These chain polyolefin resins may have a linear structure or a branched structure. As the chain olefin resin, polymethylpentene resins are preferred. Polymethylpentene resins have a relatively low dielectric constant. For this reason, by using polymethylpentene resins as a resin component, a resin film with a low dielectric constant can be obtained. Examples of commercially available polymethylpentene resins include "TPX (registered trademark)" (manufactured by Mitsui Chemicals, Inc.).
[0041] Examples of fluororesins include polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), fluorinated ethylene propylene (FEP), ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), chloroethylene trifluoroethylene copolymer, and polyvinyl fluoride (PVF). Among these, perfluoroalkoxyalkane is preferable as the fluororesin. Perfluoroalkoxyalkane has relatively low water absorption, high heat resistance, and low relative dielectric constant. Therefore, by using perfluoroalkoxyalkane as a resin component, a resin film with low water absorption, high heat resistance, and low relative dielectric constant can be obtained. Examples of commercially available fluororesins include "Fluon (registered trademark) ETFE", "Fluon (registered trademark) PTFE", "Fluon (registered trademark) PFA", and "Fluon+ (registered trademark) EA2000" (all manufactured by AGC).
[0042] As the styrene-based resin, syndiotactic polystyrene is preferable. Syndiotactic polystyrene has a relatively low dielectric constant. Therefore, by using syndiotactic polystyrene as a resin component, a resin film with a low dielectric constant can be obtained. Examples of commercially available syndiotactic polystyrene include "Oidys (registered trademark)" (manufactured by Kurabo Industries, Ltd.).
[0043] The liquid crystal polymer is not particularly limited, but examples thereof include thermotropic liquid crystal polymers, etc. Thermotropic liquid crystal polymers are aromatic polyesters synthesized mainly from monomers such as aromatic diols, aromatic dicarboxylic acids, and aromatic hydroxycarboxylic acids, and exhibit liquid crystallinity when melted.
[0044] The liquid crystal polymer preferably does not have an amide bond. Examples of thermotropic liquid crystal polymers that do not have an amide bond include 1-type liquid crystal polymers and 1.5-type (or 3-type) liquid crystal polymers. The 1-type liquid crystal polymer is a copolymer of parahydroxybenzoic acid, terephthalic acid, and dihydroxybiphenyl (copolymer of parahydroxybenzoic acid and ethylene terephthalate). The 1.5-type liquid crystal polymer is a copolymer of parahydroxybenzoic acid and 2,6-hydroxynaphthoic acid, and has a melting point between the 1-type liquid crystal polymer and the 2-type liquid crystal polymer. In this embodiment, the liquid crystal polymer is preferably a 1.5-type liquid crystal polymer. The 1.5-type liquid crystal polymer has relatively low water absorption, high heat resistance, and a low thermal expansion coefficient. Therefore, by using a 1.5-type liquid crystal polymer as a thermoplastic resin, a resin film that has low water absorption, high heat resistance, and a low thermal expansion coefficient can be obtained.
[0045] The polyimide is not particularly limited as long as it is a resin having imide bonds in the repeating unit. More specifically, the polyimide is preferably an aromatic polyimide in which aromatic compounds are directly linked by imide bonds. Polyimides have relatively high heat resistance and a low linear expansion coefficient. For this reason, they are used as thermosetting resins. TepoBy using polyimide, a resin film with high heat resistance and low thermal expansion coefficient can be obtained. Polyimide can be obtained, for example, by heat treating a polyimide precursor solution. Commercially available polyimide precursor solutions include "Uimide (registered trademark)" (manufactured by Unitika Ltd.) and "Upia (registered trademark)" (manufactured by Ube Industries, Ltd.).
[0046] The resin component according to the present embodiment preferably has a water absorption rate of 0.1% by mass or less when immersed in water at room temperature for 24 hours. Water has a relatively high dielectric constant. Therefore, if the resin component has a water absorption rate of 0.1% by mass or less, the resin composition according to the present embodiment also has a low water absorption rate. In addition, the resin film made of the resin composition is suppressed in terms of the change in dielectric constant due to moisture absorption, and can be more suitably used as a circuit board member for high frequencies.
[0047] The melting point (Tm) of the resin component according to this embodiment is preferably above 300°C. If the melting point (Tm) of the resin component is above 300°C, the melting point (Tm) of the resin composition containing this resin component is also relatively high. In addition, the resin film made of the resin composition has good heat resistance, and can be suitably used for high-voltage circuit boards. The melting point (Tm) of the resin component is measured based on the measurement of the storage modulus (E') using a dynamic viscoelasticity measuring device. Specifically, the melting point (Tm) of the resin component is the temperature of the inflection point on the high-temperature region side of the storage modulus (E').
[0048] The resin component according to the present embodiment has a dielectric constant of preferably less than 3.0, more preferably less than 2.8, and even more preferably less than 2.6, when measured by applying a high-frequency signal of 30 GHz at an ambient temperature of 25°C using a cavity resonator method in accordance with JIS R 1641. If the dielectric constant of the resin component is less than 3.0, the dielectric constant of the resin composition is also low. In addition, when the resin film according to the present embodiment is used in a high-frequency circuit board, the transmission loss in the board can be more effectively suppressed.
[0049] The resin component according to the present embodiment preferably has a dielectric loss tangent of less than 0.002, more preferably less than 0.001, when measured by applying a high-frequency signal of 30 GHz at an ambient temperature of 25° C. using a cavity resonator method in accordance with JIS R 1641. A resin composition containing a resin component having a dielectric loss tangent of less than 0.002 has a relatively low dielectric loss tangent. Therefore, when a film made of the resin composition is used in a high-frequency circuit board, the transmission loss in the board can be more effectively suppressed.
[0050] The resin component according to the present embodiment preferably has a linear expansion coefficient in the in-plane direction when formed into a film of less than 59 ppm / °C, more preferably 40 ppm / °C or less, and even more preferably 20 ppm / °C or less. If the linear expansion coefficient is less than 59 ppm / °C, the linear expansion coefficient of the resin composition containing the resin component is also relatively low. Therefore, when a circuit board is manufactured using a film made of the resin composition, warping of the circuit board can be effectively suppressed.
[0051] (Covalent organic structure) The covalent organic frameworks (COFs) contained in the resin composition according to this embodiment are porous crystalline particles in which organic structures are covalently bonded to each other to form a periodic structure, and the COFs are in powder form. Specifically, the COF according to this embodiment is a structure in which a plurality of linker parts and a plurality of multidentate core parts are connected by covalent bonds. As a result, the COF has a mesh-like molecular skeleton in which a large number of pores are formed. The multidentate core part is an organic structural part located at a branching point of the mesh-like molecular skeleton of the COF, and the linker part is an organic structural part that connects two multidentate core parts located on both sides of the linker part.
[0052] The type of covalent bond of the COF may be any of single bond, double bond, or triple bond, but is preferably a double bond from the viewpoints of both ease of synthesis of the COF and improvement of the rigidity of the COF. If the covalent bond of the COF is a double bond, the COF has a more rigid structure, and the linear expansion coefficient of the resin composition containing the COF as a filler is reduced. In addition, the covalent bond of the COF is more preferably a carbon-nitrogen double bond (imine bond) in which a carbon atom (preferably a CH group) and a nitrogen atom are bonded to each other. When the double bond between the linker part and the multidentate core part of the COF is a carbon-nitrogen double bond (imine bond), the linker part has a carbon atom (preferably a CH group) that constitutes an imine bond, and the multidentate core part has a nitrogen atom that constitutes an imine bond. Alternatively, the linker part has a nitrogen atom that constitutes an imine bond, and the multidentate core part has a carbon atom (preferably a CH group) that constitutes an imine bond.
[0053] In this embodiment, the linker part has a structure in which two atoms (i.e., nitrogen atoms or carbon atoms) constituting the imine bond are bonded to an aromatic compound, a heterocyclic compound, or a fused heterocyclic compound. The aromatic compound bonded to the atoms constituting the imine bond in the linker part preferably has one or more benzene rings, one or more fused polycyclic aromatic hydrocarbons, one or more heterocyclic aromatic compounds, or one or more fused heterocyclic aromatic compounds. Examples of the linker part include structures represented by the following chemical formulas (3) to (6). [ka] [In formula (3), n and m each independently represent an integer of 0 to 10; R 1 ~R 8 are each independently any one of hydrogen, halogen, a hydroxy group, an alkyl group, an alkoxy group, an aryl group, a phosphine group, a phosphine oxide group, and an aromatic heterocyclic group, and X is a CH group or nitrogen.
[0054] [ka] [In formula (4), n is an integer of 1 or more and 10 or less, and R 1 ~R 4 are each independently any one of hydrogen, halogen, a hydroxy group, an alkyl group, an alkoxy group, an aryl group, a phosphine group, a phosphine oxide group, and an aromatic heterocyclic group, and X is a CH group or nitrogen.
[0055] [ka] [In formula (5), R 1 ~R 6 are each independently any one of hydrogen, halogen, a hydroxy group, an alkyl group, an alkoxy group, an aryl group, a phosphine group, a phosphine oxide group, and an aromatic heterocyclic group, and X is a CH group or nitrogen.
[0056] [ka] [In formula (6), R 1 ~R 6 are each independently any one of hydrogen, halogen, a hydroxy group, an alkyl group, an alkoxy group, an aryl group, a phosphine group, a phosphine oxide group, and an aromatic heterocyclic group, and X is a CH group or nitrogen.
[0057] In the explanation of formulas (3) to (6), the alkyl group may be linear or branched, or may be a cycloalkyl group. The number of carbon atoms in the alkyl group is about 1 or more and about 20 or less. The alkoxy group may be linear or branched, or may be a cycloalkyloxy group. The number of carbon atoms in the alkoxy group is about 1 or more and about 20 or less. The aryl group is an atomic group obtained by removing one hydrogen atom from an aromatic hydrocarbon. Aryl groups include those having a condensed ring, and those having two or more independent benzene rings or condensed rings bonded directly or via a group such as vinylene.
[0058] In this embodiment, the multidentate core portion has a structure in which three or more atoms constituting the imine bond (i.e., nitrogen atoms or carbon atoms) are bonded to an aromatic compound, a heterocyclic compound, or a fused heterocyclic compound. The aromatic compound bonded to the atoms constituting the imine bond in the multidentate core portion preferably has one or more benzene rings, one or more fused polycyclic aromatic hydrocarbons, one or more heterocyclic aromatic compounds, or one or more fused heterocyclic aromatic compounds. Examples of the multidentate core portion include structures represented by the following chemical formulas (7) to (9).
[0059] [ka] [In formula (7), R 1 ~R 3 are each independently any one of hydrogen, halogen, a hydroxy group, an alkyl group, an alkoxy group, an aryl group, a phosphine group, a phosphine oxide group, and an aromatic heterocyclic group, and X is a CH group or nitrogen.
[0060] [ka] [In formula (8), R 1 ~R 15 are each independently any one of hydrogen, halogen, a hydroxy group, an alkyl group, an alkoxy group, an aryl group, a phosphine group, a phosphine oxide group, and an aromatic heterocyclic group, and X is a CH group or nitrogen.
[0061] [ka] [In formula (9), R 1 ~R 16 are each independently any one of hydrogen, halogen, a hydroxy group, an alkyl group, an alkoxy group, an aryl group, a phosphine group, a phosphine oxide group, and an aromatic heterocyclic group, and X is a CH group or nitrogen.
[0062] In the explanation of formulas (7) to (9), the alkyl group may be linear or branched, or may be a cycloalkyl group. The number of carbon atoms in the alkyl group is about 1 or more and about 20 or less. The alkoxy group may be linear or branched, or may be a cycloalkyloxy group. The number of carbon atoms in the alkoxy group is about 1 or more and about 20 or less. The aryl group is an atomic group obtained by removing one hydrogen atom from an aromatic hydrocarbon. Aryl groups include those having a condensed ring, and those having two or more independent benzene rings or condensed rings bonded directly or via a group such as vinylene.
[0063] Linker portion and / or Many The linker portion and / or the core portion preferably have a phosphorus element, for example, a phosphine group or a phosphine oxide group. Many The core part contains a phosphorus element, which can impart flame retardancy to the resin composition or improve the flame retardancy of the resin composition. Many From the viewpoint of improving the hydrophobicity of the resin composition, it is also preferable that the core portion has an alkyl group.
[0064] In this embodiment, it is preferable that both ends of the linker part are carbon atoms and the multidentate core part has a nitrogen atom, so that the covalent bond of the COF is a carbon-nitrogen double bond in which the carbon atom of the linker part and the nitrogen atom of the multidentate core part are bonded to each other. In a resin composition obtained by adding such a COF to a resin component, the carbon-nitrogen double bond in which the carbon atom of the linker part and the nitrogen atom of the multidentate core part are bonded to each other is rigid, so that an increase in the dielectric tangent is suppressed.
[0065] When the covalent bond of the COF is a carbon-nitrogen double bond in which the carbon atom of the linker part and the nitrogen atom of the multidentate core part are bonded to each other, specifically, the linker part has two carbon atoms bonded to the nitrogen atom of the multidentate core part, and the multidentate core part has three or more nitrogen atoms bonded to the carbon atom of the linker part. When the multidentate core part has three nitrogen atoms bonded to the carbon atom of the linker part, the COF can easily form a so-called two-dimensional COF skeleton having a mesh structure that spreads in a plane. In addition, since the multidentate core part has four nitrogen atoms bonded to the carbon atom of the linker part, the COF can easily form a so-called three-dimensional COF skeleton having a mesh structure that spreads three-dimensionally.
[0066] The structure of the two-dimensional COF will be described using a schematic diagram. FIG. 2 is a perspective view showing a schematic structure of a two-dimensional COF among the covalent organic frameworks according to one embodiment of the present disclosure. As shown in FIG. 2, the covalent organic framework (COF) 10 is a structure in which a plurality of linker parts 11 and a plurality of multidentate core parts 12 are linked together, and has a mesh-like skeleton. In FIG. 2, an example of a two-dimensional COF is shown as COF10, and this mesh-like skeleton spreads in a plane. Furthermore, COF10 has crystallinity, and as shown in FIG. 2, in the case of the two-dimensional COF10, a plurality of mesh skeletons spreading in a plane are arranged along a direction intersecting the plane direction in which the mesh skeleton spreads. Furthermore, a plurality of holes formed by the mesh structure are arranged along the direction in which the plurality of mesh structures are arranged. Therefore, a relatively large void is formed inside the two-dimensional COF10 by arranging a plurality of pores. The two-dimensional COF10 can hold a relatively large amount of air in the voids, and therefore has a low relative dielectric constant. Therefore, when the two-dimensional COF 10 is added to a resin component having a relatively high relative dielectric constant, a resin composition having a low relative dielectric constant relative to the resin component can be obtained.
[0067] Specific examples of COFs include structures shown in the following chemical formulas (10) to (12), but the COFs are not limited thereto.
[0068] [ka]
[0069] In the COF represented by the formula (10), the linker portion has two nitrogen atoms at both ends, and the multidentate core portion has three carbon atoms (specifically, CH groups) bonded to the nitrogen atoms at both ends of the linker portion. Therefore, the COF represented by the formula (10) has a so-called two-dimensional COF structure having a network structure that spreads in a plane.
[0070] [ka]
[0071] In the COF represented by the above formula (11), the linker portion has two carbon atoms (specifically, CH groups) located at both ends thereof, and the multidentate core portion has three nitrogen atoms bonded to the carbon atoms (specifically, CH groups) at both ends of the linker portion. Therefore, the COF represented by the above formula (10) has a so-called two-dimensional COF structure having a network structure that spreads in a plane.
[0072] [ka]
[0073] In the COF represented by the above formula (12), the linker portion has two carbon atoms (specifically, CH groups) located at both ends thereof, and the multidentate core portion has four nitrogen atoms bonded to the carbon atoms (specifically, CH groups) at both ends of the linker portion. Therefore, the COF represented by the above formula (12) has a so-called three-dimensional COF structure having a three-dimensionally expanding network structure.
[0074] The content of the covalent organic framework is preferably 10% by volume or more, more preferably 20% by volume or more, and even more preferably 30% by volume or more, relative to the resin composition. If the content of the covalent organic framework is 10% by volume or more relative to the resin composition, the linear expansion coefficient of the resin composition can be more effectively reduced, and if it is 30% by volume or more, flame retardancy can be imparted to the resin composition even when the flame retardancy of the resin component is relatively low. In addition, the upper limit of the content of the covalent organic framework is not particularly limited, but from the viewpoint of suppressing excessive increase in the rigidity of the resin film, it is preferably 80% by volume or less, more preferably 70% by volume or less, and even more preferably 60% by volume or less.
[0075] The method for producing a COF is not particularly limited, but when the covalent bond of the COF is a carbon-nitrogen double bond (imine bond), a COF can be obtained by a dehydration condensation reaction between a compound having multiple aldehyde groups and a compound having multiple amino groups. That is, a COF having an imine bond can be obtained by a dehydration condensation reaction between a linker compound having aldehyde groups at both ends and constituting the linker part of the COF by a dehydration condensation reaction with a multidentate core compound having three or more amino groups and constituting the multidentate core part of the COF by a dehydration condensation reaction. Alternatively, a linker compound having amino groups at both ends and a multidentate core compound having three or more aldehyde groups can be dehydration condensation reaction between the linker compound and the multidentate core compound. water By carrying out a condensation reaction, a COF having an imine bond is obtained.
[0076] For example, a COF represented by the structure of the above formula (10) is obtained by dehydration condensation reaction between 2,6-diaminoanthraquinone as a linker compound and 2,4,6-triformylphloroglucinol as a multidentate core compound. A COF represented by the structure of the above formula (11) is obtained by dehydration condensation reaction between terephthalaldehyde as a linker compound and 1,3,5-tris(4-aminophenyl)benzene as a multidentate core compound. A COF represented by the structure of the above formula (12) is obtained by dehydration condensation reaction between terephthalaldehyde as a linker compound and tetrakis(4-aminophenyl)methane as a multidentate core compound. The method for producing the COF represented by the structures of the above formulas (10) to (12) is not limited to the above method.
[0077] (Other additives) The resin composition according to the present embodiment may contain other additives in addition to the COF for the purpose of improving physical properties such as water absorption, heat resistance, and electrical properties. For example, the resin composition may contain an inorganic filler and an organic filler other than the COF. Examples of the inorganic filler and the organic filler include hollow silica, hollow glass, zeolite, aerogel, and silsesquioxane. The resin composition according to the present embodiment may contain only the COF as a filler.
[0078] [Manufacturing method of resin film] The method for producing the resin film is not particularly limited. A resin solution is prepared by adding a COF to a precursor solution of a resin component. ManufacturingA resin film may be obtained by applying the resin solution to a carrier film or directly applying it to another layer of a multilayer substrate, and then heating and drying the applied resin solution. A resin film may be obtained by adding a COF to a resin component that has been heated and melted, stirring the mixture to obtain a molten resin composition, and then molding the resin composition by injection molding or press molding. A resin film may also be obtained by preparing a resin composition in which a COF has been added to a resin component in advance, heating the resin composition to melt it, and then molding the resin composition by injection molding or press molding. EXAMPLES
[0079] The resin film based on the present disclosure will be described in more detail below with reference to examples, but the present invention is not limited to these.
[0080] [Preparation of covalent organic structure] First, before preparing the resin compositions according to the respective examples, three types of COFs were prepared. The specific manufacturing method of each COF is described below.
[0081] <COF(a)> In ultrapure water, 2,6-diaminoanthraquinone (Tokyo Chemical Industry Co., Ltd.) (1 mol / L) as a linker compound and 2,4,6-triformylphloroglucinol (670 mmol / L) as a multidentate core compound were stirred overnight at room temperature in the presence of p-toluenesulfonic acid monohydrate (Tokyo Chemical Industry Co., Ltd.) (5 mol / L) as an acid catalyst. The product precipitated in the mixture was then collected by filtration, thoroughly washed with ultrapure water, tetrahydrofuran, and methanol, and dried to obtain "COF(a)" as a covalent organic framework.
[0082] <COF(b)> In a mixture of 1,4-dioxane and mesitylene in a volume ratio of 4:1, terephthalaldehyde (Tokyo Chemical Industry Co., Ltd.) (37.5 mmol / L) as a linker compound and 1,3,5-tris(4-aminophenyl)benzene (Tokyo Chemical Industry Co., Ltd.) (25 mmol / L) as a multidentate core compound were stirred at room temperature for 1 hour in the presence of Sc(OTf)3 (Tokyo Chemical Industry Co., Ltd.) (1.5 mmol / L) as a Lewis acid catalyst. The product precipitated in the mixture was then collected by filtration and washed with 1,4-dioxane and mesitylene. The product was then washed with methanol for 15 hours using a Soxhlet extractor and dried to obtain "COF(b)" as a covalent organic framework.
[0083] <COF(c)> In a mixture of 1,4-dioxane and mesitylene in a volume ratio of 4:1, terephthalaldehyde (Tokyo Chemical Industry Co., Ltd.) (37.5 mmol / L) as a linker compound and tetrakis(4-aminophenyl)methane (Tokyo Chemical Industry Co., Ltd.) (18.8 mmol / L) as a multidentate core compound were stirred at room temperature for 1 hour in the presence of scandium(III) triflate (Tokyo Chemical Industry Co., Ltd.) (1.5 mmol / L) as a Lewis acid catalyst. The product precipitated in the mixture was then collected by filtration and washed with 1,4-dioxane and mesitylene. The product was then washed with methanol for 15 hours using a Soxhlet extractor and dried to obtain "COF(c)" as a covalent organic framework.
[0084] [Example 1] The above COF (b) was added to a polyimide precursor solution (trade name "U-imide (registered trademark)" manufactured by Unitika Ltd.) and stirred to prepare a resin solution. ManufacturingThis resin solution was applied to a carrier film (product name "Lumirror Film (registered trademark)", manufactured by Toray Industries, Inc.). Thereafter, the carrier film on which the resin solution was applied was heated and dried to obtain a laminate. The carrier film was removed from this laminate to obtain the resin film according to Example 1. In Example 1, the resin solution was prepared so that the content of COF(b) was 30 volume % relative to the entire resin film. Manufacturing The resin solution was then applied onto a carrier film so that the thickness of the resin film after drying would be 50 μm.
[0085] [Example 2] Syndiotactic polystyrene (SPS) (trade name "Oidys (registered trademark)", manufactured by Kurabo Industries, Ltd.) was melted, and the above-mentioned COF (b) was added to and kneaded with the molten SPS to obtain a molten resin composition. The molten resin composition was applied onto a continuous metal belt, cooled, and then peeled off from the continuous belt to obtain a resin film according to Example 2. In Example 2, SPS and COF (b) were kneaded so that the content of COF (b) was 30 volume % with respect to the entire resin film, and the molten resin composition was applied onto the continuous metal belt so that the thickness of the resin film was 50 μm.
[0086] [Example 3] First, a liquid crystal polymer was prepared. A reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser was charged with p-hydroxybenzoic acid (911 g), 4,4'-dihydroxybiphenyl (409 g), terephthalic acid (274 g), isophthalic acid (91 g), and acetic anhydride (1235 g). After the inside of the reactor was sufficiently replaced with nitrogen gas, the temperature was raised to 150°C over 15 minutes under a nitrogen gas flow, and the temperature was maintained and refluxed for 3 hours. Then, the temperature was raised to 300°C over 2 hours and 50 minutes while distilling off the by-product acetic acid and unreacted acetic anhydride. The time when the torque was increased was regarded as the end of the reaction, and the contents were taken out in a molten state into a vat to obtain a liquid crystal polyester as a liquid crystal polymer. The obtained liquid crystal polymer was cooled and pulverized with a pulverizer to obtain a liquid crystal polymer powder.
[0087] The powdered liquid crystal polymer obtained above was melted and kneaded with the COF(b) in a kneader to obtain a molten resin composition. The molten resin composition was applied onto a continuous metal belt, cooled, and peeled off from the continuous belt to obtain a resin film according to Example 3. In Example 3, the liquid crystal polymer and COF(b) were kneaded so that the content of COF(b) was 30 volume % relative to the entire resin film, and the molten resin composition was applied onto the continuous metal belt so that the thickness of the resin film was 50 μm.
[0088] [Example 4] Perfluoroalkoxyalkane (PFA) (trade name "Fulton+ (registered trademark) EA2000", manufactured by AGC) was melted, and the above-mentioned COF (b) was added to this molten PFA and kneaded in a kneader to obtain a molten resin composition. This molten resin composition was applied onto a continuous metal belt, cooled, and peeled off from the continuous belt to obtain a resin film according to Example 4. In Example 4, PFA and COF (a) were kneaded so that the content of COF (a) was 10 volume % relative to the entire resin film, and the molten resin composition was applied onto a carrier film so that the thickness of the resin film was 50 μm.
[0089] [Examples 5 to 12] Based on Table 1 shown later, resin films were prepared so that at least one of the type of covalent organic framework (COF) (COF(a), COF(b), COF(c)) and the content (volume %) of the covalent organic framework (COF) in the entire resin film was different from that of Example 4. The resin films of Examples 5 to 12 were prepared in the same manner as the resin film of Example 4, except for the type and / or content of COF.
[0090] [Example 13] A ring-opening polymer (COP) of a cyclic olefin resin (trade name "ZEONOR (registered trademark)", manufactured by Zeon Corporation) was melted, and the above-mentioned COF (b) was added to this molten COP and kneaded in a kneader to obtain a molten resin composition. This molten resin composition was applied onto a continuous metal belt, cooled, and peeled off from the continuous belt to obtain a resin film according to Example 13. In Example 13, the COP and COF (b) were kneaded so that the content of COF (b) was 30 volume % relative to the entire resin film, and the molten resin composition was applied onto a carrier film so that the thickness of the resin film was 50 μm.
[0091] [Example 14] First, an addition polymer (polynorbornene (PNB)) of a norbornene-based monomer was prepared. 16.4 g (0.07 mol) of 2-norbornene, 5.41 g (0.03 mol) of 5-hexyl-2-norbornene, 130 g of ethyl acetate as a polymerization solvent, and 115 g (0.53 mol) of cyclohexane were charged into a reaction vessel in which the polymerization atmosphere was sufficiently filled with inert gas nitrogen. Next, 0.69 g (1.4 × 10) of a transition metal catalyst (η6-toluenenickelbis(pentafluorophenyl)) was added. -3 mol) ) A catalyst solution in which the above was dissolved in 5 g of toluene was added to a reaction vessel. After stirring and polymerization for 4 hours at room temperature, the polymerization solution was added to a mixture of 47 ml of glacial acetic acid, 87 ml of 30% hydrogen peroxide, and 300 ml of pure water, and stirred for 2 hours. The aqueous layer of the solution, which was separated into the transition metal catalyst in the aqueous layer and the organic layer of the resin solution, was removed. The organic layer was further washed with pure water several times. Then, the resin solution was added to methanol, and the precipitated solid was filtered, and then dried under reduced pressure to remove the solvent, thereby obtaining polynorbornene.
[0092] The polynorbornene obtained above was dissolved in toluene and applied to a carrier film (product name "Lumirror Film (registered trademark)", manufactured by Toray Industries, Inc.) to obtain a laminate. The carrier film was removed from this laminate to obtain a resin film according to Example 14. In Example 14, PNB and COF(a) were kneaded together so that the content of COF(a) was 10 volume % relative to the entire resin film, and the molten resin composition was applied onto the carrier film so that the resin film had a thickness of 50 μm.
[0093] [Examples 15 to 22] As shown in Table 1, resin films were prepared so that at least one of the type of covalent organic framework (COF) (COF(a), COF(b), COF(c)) and the content (volume %) of the covalent organic framework (COF) relative to the entire resin film was different from that of Example 14. The resin films of Examples 5 to 12 were prepared in the same manner as the resin film of Example 14, except for the type and / or content of COF.
[0094] [Example 23] Polymethylpentene (PMP) (trade name "TPX (registered trademark)", manufactured by Mitsui Chemicals) was melted, and the above-mentioned COF (b) was added to the molten PMP and kneaded in a kneader to obtain a molten resin composition. The molten resin composition was applied onto a continuous metal belt, cooled, and peeled off from the continuous belt to obtain a resin film according to Example 23. In Example 23, COP and COF (b) were kneaded so that the content of COF (b) was 30 volume % relative to the entire resin film, and the molten resin composition was applied onto a carrier film so that the thickness of the resin film was 50 μm.
[0095] [Example 24] The resin film of Example 24 was produced in the same manner as the resin film of Example 23, except that PMP and COF(b) were kneaded together so that the content of COF(b) was 50 volume % of the entire resin film.
[0096] [Comparative Example 1] A resin film was produced without adding COF, unlike Example 1. The other production conditions were the same as those of Example 1.
[0097] [Comparative Example 2] A resin film was produced without adding COF, unlike Example 2. The other production conditions were the same as those of Example 2.
[0098] [Comparative Example 3] A resin film was produced without adding COF, unlike Example 3. The other production conditions were the same as those of Example 3.
[0099] [Comparative Example 4] A resin film was produced without adding COF, unlike in Examples 4 to 12. The other production conditions were the same as in Examples 4 to 12.
[0100] [Comparative Example 5] A resin film was produced without adding COF, unlike Example 13. The other production conditions were the same as those of Example 13.
[0101] [Comparative Example 6] A resin film was produced without adding COF, unlike Examples 14 to 22. The other production conditions were the same as those of Examples 14 to 22.
[0102] [Water absorption measurement] The water absorption rate was measured for the resin films according to Examples 1 to 24 and Comparative Examples 1 to 6. Specifically, the mass of the resin film before immersion was measured, each resin film was immersed in water at 20°C for 24 hours, and the water on the surface of each resin film was wiped off, and then the water absorption rate of each resin film was immediately measured by the Karl Fischer method. Note that the number n of each resin film was 3, and the values described below are their average values.
[0103] [Melt point (Tm) measurement] The storage modulus (E') was measured for the resin films according to Examples 1 to 24 and Comparative Examples 1 to 6, and the temperature at the inflection point of the storage modulus (E') on the high temperature region side was taken as the melting point (Tm) of the film. Specifically, the storage modulus (E') was measured using a dynamic viscoelasticity measuring device (TA-Instruments, RSA-G2) under conditions of a dry air atmosphere, a heating rate of 3°C / min, and a temperature range of -15°C to 300°C, using test pieces (thickness 50 μm) cut from the resin film to a width of 9 mm and a length of 40 mm, with a measurement length (measurement jig interval) of 20 mm.
[0104] [Measurement of relative permittivity and dielectric loss tangent] The dielectric constant and dielectric loss tangent were measured for the resin films according to Examples 1 to 24 and Comparative Examples 1 to 6. Specifically, a test piece of 30 mm×30 mm (thickness: 50 μm) was prepared for each resin film, and the dielectric constant and dielectric loss tangent of the test piece were measured by a cavity resonator method using a dielectric constant measuring device conforming to JIS R 1641. The measurement was performed by applying a high-frequency signal of 30 GHz at an ambient temperature of 25° C.
[0105] [Measurement of linear expansion coefficient] The coefficient of linear expansion (CTE) in the in-plane direction was measured for the resin films according to Examples 1 to 24 and Comparative Examples 1 to 6. Specifically, a 200 mm×50 mm test piece (50 μm thick) was prepared for each resin film, and the coefficient of linear expansion in the in-plane direction (XY direction) was measured by a TMA (thermomechanical analysis) method in accordance with JIS K 7197. The TMA conditions were as follows: using a thermal analyzer (TMA4030SA, manufactured by Bruker), the temperature was raised from room temperature to 150° C. at a rate of 10° C. / min under a nitrogen atmosphere, and the load was 10 g.
[0106] [Flame retardancy evaluation] For the resin films according to Examples 1 to 24 and Comparative Examples 1 to 6, a test piece of 200 mm×50 mm (thickness 50 μm) was prepared based on the UL94 standard, and a thin material vertical combustion test (ASTM D4804) was carried out on the test piece to evaluate the flame retardancy. In Table 1, the resin films whose flammability classification according to the UL standard was VTM-0, VTM-1 or VTM-2 were evaluated as having flame retardancy "yes," and the resin films in which the sample burned out during the test were evaluated as having flame retardancy "no."
[0107] The evaluation results for each of the resin films according to Examples 1 to 24 and Comparative Examples 1 to 6 are shown in Tables 1 and 2, respectively.
[0108] [Table 1]
[0109] [Table 2]
[0110] As shown in Tables 1 and 2, comparing Example 1 and Comparative Example 1, both of which have polyimide (PI) resin components, the resin film of Comparative Example 1, which does not contain COF, has a relatively high relative dielectric constant of 3.8, while the resin film of Example 1, which contains COF, has a relative dielectric constant of 3.0. The coefficient of linear expansion (CTE) of Comparative Example 1 was less than 20 ppm / °C, and that of Example 1 was also less than 20 ppm / °C, both of which were relatively low values.
[0111] In addition, comparing Example 2 and Comparative Example 2, both of which have syndiotactic polystyrene (SPS) as resin components, the resin film of Comparative Example 2, which does not contain COF, has a relatively high CTE of 70 ppm / ° C., while the resin film of Example 2, which contains COF, has a CTE of 51 ppm / ° C. The relative dielectric constant of Comparative Example 2 was 2.3, and the relative dielectric constant of Example 2 was 2.2, both of which are relatively low values.
[0112] In addition, comparing Example 3 and Comparative Example 3, both of which have liquid crystal polymer resin components, the resin film of Comparative Example 3, which does not contain COF, has a relatively high relative dielectric constant of 3, while the resin film of Example 3, which contains COF, has a relative dielectric constant of 2.6. The CTEs of Comparative Example 3 and Example 3 were both less than 20 ppm / °C, which were relatively low values.
[0113] In addition, comparing Examples 4 to 12, all of which have perfluoroalkoxyalkane (PFA) resin components, with Comparative Example 4, the resin film of Comparative Example 4, which does not contain COF, has a relatively high CTE of 152 ppm / ° C., while the resin films of Examples 4 to 12, which contain COF, have CTEs of 79 ppm / ° C. to 133 ppm / ° C. The relative dielectric constant of Comparative Example 4 was 2.1, and the relative dielectric constants of Examples 4 to 12 were 2.0 to 2.2, both of which were relatively low values.
[0114] In addition, comparing Example 13 and Comparative Example 5, both of which have resin components that are ring-opening polymers (COP) of cyclic olefin resins, the resin film of Comparative Example 5, which does not contain COF, has a relatively high CTE of 71 ppm / ° C., while the resin film of Example 13, which contains COF, has a CTE of 53 ppm / ° C. The relative dielectric constant of Comparative Example 5 was 2.3, and the relative dielectric constant of Example 13 was 2.2, both of which are relatively low values.
[0115] In addition, comparing Examples 14 to 22, all of which have polynorbornene (PNB) as the resin component, with Comparative Example 6, the resin film of Comparative Example 6, which does not contain COF, had a relatively high CTE of 59 ppm / ° C., while the resin films of Examples 14 to 22, which contained COF, had CTEs of 20 ppm / ° C. to 52 ppm / ° C. The relative dielectric constant of Comparative Example 6 was 2.3, and the relative dielectric constants of Examples 14 to 22 were 2.1 to 2.3, both of which were relatively low values.
[0116] The resin films according to Examples 23 and 24, in which the resin component was polymethylpentene (PMP), had relatively low dielectric constants of 2.0 and 2.1, respectively. Furthermore, it is presumed that the resin films according to Examples 22 and 23, which contained PMP, also contained COF, and thus had relatively low CTEs of 35 ppm / °C and 29 ppm / °C, respectively.
[0117] As described above, in each example, the COF has a mesh-like molecular skeleton containing air with a low dielectric constant, so when the dielectric constant of the resin component is relatively high, the dielectric constant of the resin composition is lower than that of the resin component. Furthermore, the mesh-like molecular skeleton of the COF has covalent bonds and is rigid, so when the linear expansion coefficient of the resin component is relatively high, the linear expansion coefficient of the resin composition is lower than that of the resin component. Therefore, the resin film according to this example was suitable for use in a multilayer substrate.
[0118] Furthermore, in comparison with the resin films according to Examples 4 to 12, when the COF was COF(b) or COF(c), that is, when the covalent bond of the COF was a carbon-nitrogen double bond in which the carbon atom of the linker part and the nitrogen atom of the multidentate core part were bonded to each other, the dielectric loss tangent of the resin composition was suppressed from increasing relative to the resin component. The same tendency was also obtained in Examples 14 to 22.
[0119] Furthermore, when comparing the resin films according to Examples 14 to 22 with those according to Comparative Example 6, when the content of COF in the resin composition was 30 volume % or more, the resin composition was provided with flame retardancy by containing COF. Similar trends were also observed between Example 2 and Comparative Example 2, and between Example 13 and Comparative Example 5.
[0120] In the above description of the embodiments, configurations that can be combined may be combined with each other.
[0121] [Note] As described above, the present embodiment includes the following disclosure.
[0122] <1> A resin component, A resin film comprising a resin composition comprising: a covalent organic framework in which a plurality of linker portions and a plurality of multidentate core portions are linked by covalent bonds.
[0123] <2> The resin component is a thermoplastic resin. <1> The resin film according to claim 1.
[0124] <3> The water absorption rate of the resin component is 0.1% by mass or less. <1> or <2> The resin film according to claim 1.
[0125] <4> The melting point of the resin composition is greater than 300°C. <1> from <3> 13. The resin film according to claim 12 .
[0126] <5> The resin composition has a relative dielectric constant of less than 3.0. <1> from <4> 13. The resin film according to claim 12 .
[0127] <6> The resin composition has a dielectric loss tangent of less than 0.002. <1> from <5> 13. The resin film according to claim 12 .
[0128] <7> The resin component is a thermoplastic resin, The resin composition has a water absorption rate of 0.1% by mass or less, The melting point of the resin composition is greater than 300° C., The resin composition has a relative dielectric constant of less than 3.0; The resin composition has a dielectric loss tangent of less than 0.002. <1> The resin film according to claim 1.
[0129] <8> The resin component is an addition polymer of a norbornene-based monomer. <1> from <7> 13. The resin film according to claim 12 .
[0130] <9> The covalent bond of the covalent organic framework is a carbon-nitrogen double bond. <1> from <8> 13. The resin film according to claim 12 .
[0131] <10> Both ends of the linker portion have carbon atoms, The multidentate core portion has a nitrogen atom, The covalent bond of the covalent organic framework is a carbon-nitrogen double bond in which a carbon atom of the linker portion and a nitrogen atom of the multidentate core portion are bonded to each other. <9> The resin film according to claim 1.
[0132] <11> The content of the covalent organic framework in the resin composition is 10% by volume or more and 70% by volume or less. <1> from <10> 13. The resin film according to claim 12 .
[0133] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Industrial Applicability]
[0134] The resin film according to the present disclosure can be suitably used as a low dielectric layer contained in a multilayer resin substrate such as a flexible substrate or a rigid substrate (particularly a high frequency circuit substrate). [Explanation of symbols]
[0135] 1 Resin film, 10 Covalent organic framework (COF), 11 Linker part, 12 Multidentate core part.
Claims
1. A resin component, a covalent organic framework in which a plurality of linker portions and a plurality of multidentate core portions are linked by covalent bonds; The resin component has a water absorption rate of 0.1% by mass or less, The resin film, wherein the melting point of the resin composition is higher than 300°C.
2. The resin film according to claim 1 , wherein the resin component is a thermoplastic resin.
3. A resin component, a covalent organic framework in which a plurality of linker portions and a plurality of multidentate core portions are linked by covalent bonds; The resin component has a water absorption rate of 0.1% by mass or less, The resin film, wherein the resin composition has a relative dielectric constant of less than 3.
0.
4. A resin component, a covalent organic framework in which a plurality of linker portions and a plurality of multidentate core portions are linked by covalent bonds; The resin component has a water absorption rate of 0.1% by mass or less, The resin film, wherein the resin composition has a dielectric loss tangent of less than 0.
002.
5. A resin component, a covalent organic framework in which a plurality of linker portions and a plurality of multidentate core portions are linked by covalent bonds; The resin component has a water absorption rate of 0.1% by mass or less, The resin component is a thermoplastic resin, The melting point of the resin composition is greater than 300° C., The resin composition has a relative dielectric constant of less than 3.0, The resin film, wherein the resin composition has a dielectric loss tangent of less than 0.
002.
6. A resin component, a covalent organic framework in which a plurality of linker portions and a plurality of multidentate core portions are linked by covalent bonds; The resin component has a water absorption rate of 0.1% by mass or less, The resin film, wherein the resin component is an addition polymer of a norbornene-based monomer.
7. The resin film according to claim 1 , wherein the covalent bond of the covalent organic framework is a carbon-nitrogen double bond.
8. A resin component, a covalent organic framework in which a plurality of linker portions and a plurality of multidentate core portions are linked by covalent bonds; The resin component has a water absorption rate of 0.1% by mass or less, the covalent bond of the covalent organic framework is a carbon-nitrogen double bond, Both ends of the linker portion have carbon atoms, The multidentate core portion has a nitrogen atom, the covalent bond of the covalent organic framework is a carbon-nitrogen double bond in which a carbon atom of the linker portion and a nitrogen atom of the multidentate core portion are bonded to each other.
9. A resin component, a covalent organic framework in which a plurality of linker portions and a plurality of multidentate core portions are linked by covalent bonds; The resin component has a water absorption rate of 0.1% by mass or less, A resin film, wherein a content of the covalent organic framework relative to the resin composition is 10 volume % or more and 70 volume % or less.
Citation Information
Patent Citations
Covalent organic framework membrane and preparation method thereof, and applications of covalent organic framework membrane in identification of chiral amines
CN110791046A
Protective film as well as preparation method and application thereof
CN113122008A
JP1974067116A
Denkibuhinno taiatsushikenhoho
JP1976099569A
Hierarchical encoding and decoding device for digital image signal
JP1995099646A